Total three-dimensional imaging of phase objects using defocusing microscopy: Application to red blood cells - Roma, P. M. S.; Siman, L.; Amaral, F. T.; Agero, U.; Mesquita, O. N. (Applied physics letters, 2014)
We introduce Defocusing Microscopy (DM), a bright-field optical microscopy technique able to perform total three-dimensional (3D) imaging of transparent objects. By total 3D imaging, we mean the determination of the actual shapes of the upper and lower surfaces of a phase object. We propose a methodology using DM and apply it to red blood cells subject to different osmolality conditions: hypotonic, isotonic, and hypertonic solutions. For each situation, the shapes of the upper and lower cell surface-membranes (lipid bilayer/cytoskeleton) are completely recovered, displaying the deformation of red blood cell (RBC) surfaces due to adhesion on the glass-substrate. The axial resolution of our technique allowed us to image surface-membranes separated by distances as small as 300 nm. Finally, we determine the volume, surface area, sphericity index, and RBC refractive index for each osmotic condition.